Case report: KETOLAND the psychoeducation program for ketogenic diet - Zanaboni, Martina Paola; Pasca, Ludovica; Geraci, Maria Angela; Varesio, Costanza; Guglielmetti, Monica; Tagliabue, Anna; Grumi, Serena; De Giorgis, Valentina (Frontiers in Psychiatry, 2023)
Glucose transporter type 1 deficiency syndrome (GLUT1DS) is a rare neurological disorder characterized by a wide spectrum of symptoms: epilepsy, movement disorders and neurocognitive impairment. The gold standard treatment for GLUT1DS are ketogenic dietary therapies (KDTs), specifically classical ketogenic diet (CKD). Despite the benefits, CKD often represents a challenge for patients and their families since meal preparation is extremely demanding and deviates a lot from normal diet. To assure an optimal compliance to CKD, a psychological support for parents and patients with GLUT1DS is highly recommended. The aim of this case report is to investigate the effectiveness of a psychoeducational program, partially implemented through telepsychology, based on the theoretical model of Cognitive Behavioral Play Therapy to support KDT knowledge and adherence in a patient with GLUT1DS and intellectual disability and her family.